Modeling brightness temperature of prominences on the solar disk using ALMA single-dish observations - Matković, Filip; Brajša, Roman; Benz, Arnold O.; Ludwig, Hans-Günter; Selhorst, Caius L.; Skokić, Ivica; Sudar, Davor; Hanslmeier, Arnold (Astronomische Nachrichten, 2025)
Prominences (PRs) are among the most common solar phenomena, yet their full physical picture, particularly their chromospheric mm emission, remains incomplete. The new Atacama Large Millimeter/submillimeter Array (ALMA) presents an opportunity to study PRs at mm and sub-mm wavelengths through a combination of measurements and theoretical modeling. We utilize ALMA single-dish measurements alongside data from other radio instruments to model the PR brightness temperature through adaptation and modification of the 1D semi-empirical Avrett-Tian-Landi-Curdt-Wülser (ATLCW) quiet-Sun (QS) model. The calculated and measured PR brightness temperatures were found to be lower than the measured QS value and predictions from the unperturbed ATLCW QS model across the ALMA wavelength range, consistent with PRs appearing in absorption. The PR density was found to be 60-163 times higher and temperature 155-163 times lower than the QS level, aligning with previous measurements. A key finding emerged with the non-hydrostatic equilibrium assumption, yielding a more physically consistent PR brightness temperature. This suggests that PR stability is most likely maintained by its magnetic field obeying magnetostatic conditions rather than by pure hydrostatic equilibrium, supporting recent studies. Additionally, our results confirm that thermal bremsstrahlung is the dominant radiation mechanism for PRs at mm and sub-mm wavelengths.
Gesehen am 02.02.2026
Veröffentlicht: 10 September 2025